Emotional Intelligence and Personality Traits Based on Academic Performance - Dong, Xin; Kalugina, Olga A.; Vasbieva, Dinara G.; Rafi, Arslan (Frontiers in Psychology, 2022)
The purpose of this study is to examine the role of personality traits based on academic performance. Furthermore, this study also aims at exploring the effect of the students’ virtual experience education and productivity influenced by their personality as well as their emotional intelligence abilities. The participants of this research are university students studying in Pakistan and Russia. Thus, the sample comprises of bachelors and master’s students. Existing scales are adopted with minor changes to make it more suitable and understandable within the study context. In total 319 questionnaires were distributed. Among these 365 questionnaires, 234 questionnaires were received and further used with the purpose of data analysis. This shows an encouraging response from the targeted sample. The students’ education and productivity are influenced by their personality as well as their emotional intelligence abilities. The findings imply that being extrovert is a strong predictor of the students’ achievement and should be prioritized in intervention strategies. This personality feature is responsible for performance in addition to virtual learning experience. Despite its low overall relative value, agreeableness is a significant driver of the students’ achievement. Along with ability and aptitude assessments, personality evaluations might be utilized as a secondary screening tool to identify adolescents at risk of underperformance and academic performance failure. Therefore, learning emotional skills would be beneficial to cope with the modern challenges of the competitive educational environment. Virtual experience and being emotionally sound can help students to learn quickly and to be more adaptive to the new world of digitalization. The conclusions of the present study have significant implications for educators and policymakers. They should admit that boosting emotional intelligence levels through teaching or training is a significant objective of contemporary education. Students' emotional intelligence abilities related to culture may be shown in a variety of ways, from expectations toward students to interpersonal interactions among students, and from teaching techniques to evaluation methods.